The adaptation process of a safety planning intervention to promote connectedness and reduce distress in Diné adolescents and adults during the COVID-19 pandemic - Allison-Burbank, Joshuaa Dominic; Begaye, Vanessa; Dedman-Cisco, Kyann; Jim, Lisa; Archuleta, Shannon; Begay, Renae; Howe, Lacey; Haroz, Emily E. (Frontiers in Public Health, 2025)
Indigenous connectedness is an impetus for health, well-being, self-confidence, cultural preservation, and communal thriving. When this connectedness is disrupted, the beliefs, values, and ways of life that weave Indigenous communities together is threatened. In the Spring of 2020, the COVID-19 virus crept into Tribal Nations across the United States and exacerbated significant health-related and educational inequities. The first case of COVID-19, or Dikos Ntsaaígíí-19 in the Diné (Navajo) language, arrived in the Southwest in March 2020. The virus quickly spread amongst Diné communities and contributed to immediate school closures. These closures created significant disruption to connectedness on the Navajo Nation. Methods: As part of the Community Based Participatory Research process, our team worked with a Community Advisory Board (CAB) to facilitate a longitudinal cohort study titled “Project SafeSchools” and, most critically, to culturally adapt mental health interventions to be implemented as a part of this study. This paper describes the process our team used to select, adapt, and test Safety Planning and Caring Contacts interventions to reduce elevated rates of depression, anxiety, and suicidal ideation amongst Diné adolescents and adults. CBPR was the primary approach used to engage with Navajo Nation communities and the adaptation process was guided by a scoping study of frameworks for adapting public health evidence-based interventions (EBI) and was guided by the cultural adaptation process of Ward et al (2022). Our team met virtually several times in 2021 and 2022 as the parent launched and as the pilot randomized clinical trial called “+Connection is Medicine” started. When Safety Planning and Caring Contacts messaging was selected, the study team, which consisted primarily of Navajo research personnel led by a Navajo community-based principal investigator (PI) and allied PIs with extensive experience in implementation science, infectious disease prevention, and CBPR, were adapted and presented to CAB members. This CAB also included a youth advisory council who participated in the field testing and further adaptation process.